Measurement of the entrainment window of islets of Langerhans by microfluidic delivery of a chirped glucose waveform. Issue 9 (1st September 2015) - Dhumpa, Raghuram; Truong, Tuan M.; Wang, Xue; Roper, Michael G.
<x xml:space="preserve">Abstract</x> A microfluidic device was used to deliver chirped glucose waves to find the entrainment regions of islets of Langerhans.